2020
DOI: 10.1080/19371918.2020.1806985
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Nigeria: Knowledge and compliance with preventive measures

Abstract: The novel coronavirus pandemic has upended the world as we knew it and is a concern for governments globally. With cases still surging in different regions around the globe, the level of knowledge of COVID-19 and compliance with preventive measures still differ across cultural regions. Our study explored knowledge of COVID-19 and compliance with preventive measures among community members in Anambra State, Nigeria, using in-depth interviews (IDI). Data were sourced from 36 persons comprising 30 household heads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 24 publications
6
21
1
Order By: Relevance
“…While, other studies showed that beliefs and knowledge of COVID-19 were correlated with compliance to preventive measures [ 15 , 16 , 21 ], this study did not find a significant association. This could be due to 90% of respondents perceived COVID-19 to be serious threat as indicated by their belief in that it could kill anyone.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…While, other studies showed that beliefs and knowledge of COVID-19 were correlated with compliance to preventive measures [ 15 , 16 , 21 ], this study did not find a significant association. This could be due to 90% of respondents perceived COVID-19 to be serious threat as indicated by their belief in that it could kill anyone.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies investigating compliance of public health and social measures to prevent the spread of COVID-19 have so far shown a spectrum of compliance to such measures [14][15][16][17][18][19][20][21][22]. Reasons for compliance, or lack thereof, to prevention measures have included attitudes to the prevention measures, perceived risk of the virus to the individual, belief in the existence of the virus, law enforcement and / or penalties imposed due to non-compliance, availability and ease of access to protective measures (e.g., face masks, running water and soap, hand sanitiser), and availability and accessibility of alternative work and travel arrangements [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating KAP related to COVID-19 can help to identify gaps and inform future education and behavior change interventions targeting the general population as well as healthcare providers. Of the few studies that have measured COVID-19 KAP in SSA, many had limitations in their sampling procedures (e.g., through facility-based 17,18 or Internet-based recruitment 19 ) and population segments surveyed (e.g., with unrepresentative or small sample sizes 20 ), and very few multisite studies have been conducted to examine potential differences across countries. Some studies among the general population have found low knowledge of COVID-19 in countries such as the Democratic Republic of the Congo.…”
Section: Introductionmentioning
confidence: 99%
“…21 However, others have identified low compliance with recommended health measures and preventive practices despite knowledge of COVID-19 in countries such as Egypt, Nigeria, and Sudan. 20,22,23 A study performed in Sierra Leone found a strong association between knowledge and practices, but that deficits in each leave many people at risk. 24 Among healthcare providers, most current data regarding KAP as well as experiences dealing with COVID-19 in facilities and communities are limited to certain specialties in specific locations.…”
Section: Introductionmentioning
confidence: 99%